Impact of Farm Diversification on Income- A Village Study in Shiwalik Foothills in Himachal Pradesh - Arya, Swarn Lata; Yadav, R.P. (Journal of Soil and Water Conservation, 2022)
The present study was undertaken to examine the impact of technology transfer programme on the extent and pattern of diversification in a village situated in the foothills of Shivaliks in Solan district of Himachal Pradesh. After the introduction of irrigation facilities along with various improved production technologies, alternative land uses, farmers were encouraged to grow more number of crops to achieve higher levels of income. As a result of crop diversification, the net returns per hectare increased from Rs.7, 448/- before the project period to Rs.24, 590/- after the project implementation. Herfindahl index was used to measure the extent of diversification, which revealed that 67 percent of the farmers were largely diversified after the project. The regression analysis indicated that diversification with high value crops is possible only when certain pre-conditions are met, like availability of irrigation, modern inputs, market density, and supply of institutional credit etc.